A Hyphenated Preconcentrator-Infrared-Hollow-Waveguide Sensor System for N2O Sensing - Da Silveira Petruci, João Flavio [UNESP]; Wilk, Andreas; Cardoso, Arnaldo Alves [UNESP]; Mizaikoff, Boris (Springer Nature, 2018)
Following the Kyoto protocol, all signatory countries must provide an annual inventory of greenhouse-gas emission including N2O. This fact associated with the wide variety of sources for N2O emissions requires appropriate sensor technologies facilitating in-situ monitoring, compact dimensions, ease of operation, and sufficient sensitivity for addressing such emission scenarios. In this contribution, we therefore describe an innovative portable mid-infrared chemical sensor system for quantifying gaseous N2O via coupling a substrate-integrated hollow waveguide (iHWG) simultaneously serving as highly miniaturized mid-infrared photon conduit and gas cell to a custom-made preconcentrator. N2O was collected onto a solid sorbent material packed into the preconcentrator unit, and then released via thermal desorption into the iHWG-MIR sensor utilizing a compact Fourier transform infrared (FTIR) spectrometer for molecularly selective spectroscopic detection with a limit of detection (LOD) at 5 ppbv. Highlighting the device flexibility in terms of sampling time, flow-rate, and iHWG design facilitates tailoring the developed preconcentrator-iHWG device towards a wide variety of application scenarios ranging from soil and aquatic emission monitoring and drone- or unmanned aerial vehicle (UAV)-mounted monitoring systems to clinical/medical analysis scenarios.